2022
DOI: 10.1111/evo.14414
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sibling cooperation in presence and absence of parental care in a genus with interspecific variation in offspring dependence

Abstract: The widely spread evolutionary strategy of parental care is considered an important driver of social evolution. Although offspring were long thought to primarily interact competitively, recent studies revealed the potential importance of sibling cooperation. Theories suggest that the degree of cooperation in offspring interactions depends on the degree of offspring dependence on parental care: offspring unable to forage on their own should compete more, whereas more independent juveniles may increase the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…However, currently there is only mixed evidence for sibling cooperation in N. vespilloides . A study of Magneville et al ( 2018 ), for example, did not find any positive effect of brood size on offspring performance and Prang et al ( 2022 ) only found signs of sibling cooperation when larvae developed on a parentally unprepared carcass. Interestingly, the study of Schrader et al ( 2015 ) found a positive effect of brood size on offspring mass only in the absence of parents, but not under biparental care.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, currently there is only mixed evidence for sibling cooperation in N. vespilloides . A study of Magneville et al ( 2018 ), for example, did not find any positive effect of brood size on offspring performance and Prang et al ( 2022 ) only found signs of sibling cooperation when larvae developed on a parentally unprepared carcass. Interestingly, the study of Schrader et al ( 2015 ) found a positive effect of brood size on offspring mass only in the absence of parents, but not under biparental care.…”
Section: Discussionmentioning
confidence: 98%
“…If the number of larvae per gram carcass is very high, the larvae inevitably compete for food, because there is a limited amount of food available for each larva. If larval density is low, they benefit from having siblings because collectively they are more efficient in utilizing the resource (Prang et al, 2022 ). However, currently there is only mixed evidence for sibling cooperation in N. vespilloides .…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing number of studies reveal that sibling interactions are not competitive by default and may include a great diversity of cooperative interactions providing direct and indirect (due to relatively high genetic relatedness) benefits to siblings (Kramer & Meunier, 2019;Roulin & Dreiss, 2012). For instance, offspring postpone fledging to the benefit of their younger siblings in the house wren, Troglodytes aedon (Bowers et al, 2013), form coalitions with litter mates against unrelated juveniles in the spotted hyaena, Crocuta crocuta (Smale et al, 1995), express mutual cleaning in the ambrosia beetle Xyleborinus saxesenii (Biedermann & Taborsky, 2011), and may cooperate to improve foraging success in the absence of parents in the burying beetle Nicrophorus vespilloides (Prang et al, 2022;Rebar et al, 2020; but see Magneville et al, 2018). Having access to these benefits can have a profound impact on offspring fitness and may thus ultimately favour the maintenance of family life, particularly when parental care is facultative, a phenomenon that probably prevailed in the early evolution of family life (Falk et al, 2014) and (still) prevails in contemporary precocial species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Prang et al. ( 2021 ) propose to test if the degree of sibling cooperation depends on the degree of offspring dependence on parental care using three burying beetle species differing in dependence on parental care, with N. orbicollis being the most dependent, N. vespilloides intermediately dependent, and N. pustulatus the least dependent. Prang et al.…”
mentioning
confidence: 99%
“… Simplified generalized graphical representation of the patterns described by Prang et al. ( 2021 ) that illustrates that (A) brood size improves larval performance on non‐prepared but not on (B) prepared carcasses. Larvae of dependent species showed (C) higher growth and survival rates on non‐prepared carcasses, but not on (D) carcasses with pre‐hatching care, whereas larvae of independent species showed high survival rates throughout.…”
mentioning
confidence: 99%